Protective effect of chard extract on glycoprotein compounds and enzyme activities in streptozotocin-induced hyperglycemic rat lungs - (:unkn) unknown (BULGARIAN ACAD SCIENCE, 2018)
In the present study, the protective effect of chard on glycoproteins, hydroxyproline, advanced oxidation protein products and enzyme activities in the lung tissue of streptozotocin (STZ) - induced hyperglycemic rats were examined. Male, Sprague Dawley rats were grouped as control, hyperglycemic, chard, insulin, chard+insulin given hyperglycemic rats. Hyperglycemia was induced by as a single dose of STZ (60 mg/kg) administered intraperitoneally. Fourteen days after the rats were made hyperglycemic, chard extract was administered to rats 2 g/kg/day by gavage and/or insulin a dose of 6U/kg/day for 45 days. Glycoprotein components, prolidase activity and levels of hydroxyproline and advanced oxidation protein products were significantly increased in the lung tissues of hyperglycemic rats; on the other hand, paraoxonase and arylesterase activities were decreased. Treatment with chard and/or insulin reversed these effects. These results suggested that chard possesses a significant beneficial effect on abnormal glycoprotein metabolism and enzyme activities in STZ-induced hyperglycemic rats.
Keywords: chard; glycoprotein; hyperglycemic; lung; rat; SERUM PROLIDASE ACTIVITY; INDUCED OXIDATIVE STRESS; VAR. CICLA EXTRACT; DIABETIC-RATS; PARAOXONASE ARYLESTERASE; ASSOCIATION; MEMBRANE; MARKERS; PLASMA; DAMAGE